Pengembangan Metode ISAKE Social Research Design - Dedy Febry Rachman; Syaiful Amri (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
The purpose of this research development is expected to produce a product of social research methods: 1). Learning devices, 2). Learning assessment / evaluation guidelines, 3). Product social research methods, based on the identification of learning objectives by considering the curriculum that has been applied namely the development of material from the 2013 curriculum on the material